Change of cystine/glutamate antiporter expression in ethanol-dependent rats - Peana, Alessandra T.; Muggironi, Giulia; Bennardini, Federico (Frontiers in Neuroscience, 2014)
Background: Some drugs of abuse down regulate the expression of cystine/glutamate (xCT) antiporter in the nucleus accumbens (Acb) after extinction or withdrawal. The altered level of xCT exchanger in Acb, a structure involved in ethanol reinforcement, may contribute to the pathological glutamatergic signalling, linked to addiction. We hypothesised that the expression of xCT may be changed in Acb and whole brain also in non-dependent (occasional drinkers), ethanol-dependent rats, as well as, during ethanol withdrawal. Methods: Wistar rats were made ethanol-dependent by chronic exposure to an alcoholic milk beverage (from 2.4 to 7.2% v/v ethanol). Ethanol non-dependent rats were exposed to a similar, but non-alcoholic liquid diet and self-administered ethanol (10%) twice a week. Withdrawal in ethanol-dependent rats was studied at 12 hours after the last ethanol-enriched diet exposure. Immediately after the measurement of somatic signs of withdrawal, Western blot analysis with a polyclonal antibody against xCT was carried out in a naïve control group, non-dependent and ethanol-dependent rats as well as withdrawal rats, in order to study the level of xCT expression in Acb and whole brain. Results. Non-dependent rats self-administered an average dose of 1.21±0.02 g/kg per session (30 min). Daily ethanol consumption during chronic exposure to the alcoholic beverage ranged from 6.30±0.16 to 13.99±0.66 g/kg. Ethanol dependent rats after suspension of the ethanol-enriched diet have shown significant somatic signs of withdrawal. Western blotting analysis of Acb lysates revealed that xCT was over expressed in ethanol-dependent rats whereas in whole brain preparations xCT was over expressed in both non-dependent and ethanol-dependent rats compared to control group. On the contrary, xCT expression during withdrawal was down regulated in Acb and restored to control level in whole brain preparations. Conclusions: The changes of xCT expression in both Acb and whole brain followin